2019
DOI: 10.2147/ndt.s206771
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of psychiatric comorbidity on the severity, short-term functional outcome, and psychiatric complications after acute stroke</p>

Abstract: Background and purpose The comorbidity of psychiatric disorders and cerebrovascular disease appears to be complex with underlying bidirectional influences. Hitherto, research has focused mainly on the evaluation of stroke risk in particular psychiatric disorders; only a few studies have assessed their role in the acute natural history of stroke. The aim of this study was to provide a perspective on psychiatric premorbidity and its impact on stroke severity, psychiatric complications during the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 67 publications
0
19
0
1
Order By: Relevance
“…Another etiology for the increased stroke severity and worse outcome was attributed, by a systematic review, to increased stress and depression during the pandemic. Psychosocial stressors have been associated with more severe strokes and poor outcome [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another etiology for the increased stroke severity and worse outcome was attributed, by a systematic review, to increased stress and depression during the pandemic. Psychosocial stressors have been associated with more severe strokes and poor outcome [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other types of comorbidity such as a co-existent psychiatric disorder, may also contribute to higher degrees of actual or perceived social isolation. Notably, there is a distinct female predominance in depression prevalence [ 18 ], and associations between pre-existing depressive disorder as well as other psychiatric comorbidities with short- and long-term post-stroke outcomes [ 19 , 20 ] have been noted earlier, thus identifying another important area in need for interdisciplinary preventative strategies. Finally, previous studies found an association between living alone, risk of stroke [ 21 ] as well as a delayed presentation with symptoms of stroke [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These psychological disorders could be expected to impose more challenges in stroke care. Several studies have reported associations of psychological distress with more severe strokes and a higher prevalence of a poorer outcome [ 22 ]. Interestingly, our study suggested that stroke severity and stroke outcome were constant across the two periods despite the possibility that the stroke patients involved may have experienced some degree of psychological dysfunction.…”
Section: Discussionmentioning
confidence: 99%